Improving the effectiveness of market-oriented organisation: Empirical evidence from an emerging economy. (May 2017) - Bucic, Tania; Ngo, Liem Viet; Sinha, Ashish
In the context of an emerging market economy, this study examines the mediating role of marketing capabilities on the market orientation (MO)–performance relationship. Specifically, the authors investigate the roles of product innovativeness, customer relationship management (CRM) capability, research and development (R&D) integration and brand management capabilities in the institutionalisation of a MO culture and the implementation of MO behaviours. With data collected from 150 organisations, the authors find that MO behaviour fully mediates the effects of MO culture on product innovativeness and CRM capability, which in turn enhance firm performance. In addition, leadership quality facilitates the effect of MO culture on MO behaviour, and the effects of product innovativeness and CRM capability on firm performance are greater in the presence of R&D–marketing integration and brand management capabilities, respectively.